MICROLEAKAGE ASSOCIATED WITH RETROGRADE FILLING AFTER ROOT END RESECTION (in vitro study) - Elka Radeva; Tsonko Uzunov; Dimitar Kosturkov (Peytchinski Publishing, 2014)
The purpose of the study is to compare microleakage after root end resection of the two materials (MTA and Biodentine) for two different apical cavity preparation using the method of penetration of dye - 0, 2 % Rodamine B. Materials and Methods: Forty-eight extracted single-rooted human teeth were used in this study. The resection was made at 3 mm from the root tip with a high speed diamond bur at an angle of 90 degree to the long axis of the tooth. For the retrofilling, ProRoot MTA and Biodentine were used. The teeth were divided into 5 groups: 1st group (10 teeth) - the apical cavity was prepared with stainless steel fissure bur #10 at 3 mm depth in the root canal parallel to the long axis of the tooth and is filled retrograde with MTA. 3rd group (10 teeth) - retrofilling with Biodentine. 2 nd group (10 teeth) - with a round bur apical cavity was prepared with a concave shape and cavity along the root canal with a depth of 3 mm and retrograde obturation with MTA. 4th group (10 teeth) - retrofilling with Biodentine. 5th group (8 teeth) - control group - with preparation of the cavity after resection without retrofilling. The outer surface of the root is covered with two layers of varnish, with the exception of the apical 3 mm then immersed in 0.2% Rodamine B for 72 h. The degree of penetration of the dye is measured in millimeters. Results: Relative highest median value of penetration of the dye in mm is in the control group. MTA group has a higher value in mm versus the Biodentine. The apical preparation with a concave shape and cavity along the root canal with a depth of 3 mm after apicoectomy is important to reduce apical microleakage. Conclusion: Different apical cavity preparations in both types of material have led to the microleakage dye, but to varying degrees.